Nursing Faculty Shortage Impact on Nursing Students: A Descriptive Phenomenological Study - Asia Antig; Shaniah Arañez; Chariemae Cañazares; Daisy Palompon (Nursing Research and Practice)
Conclusion: The findings underscore the critical need for immediate and comprehensive measures to address the nursing faculty shortage. Despite compensatory efforts by the institution, the impact on learning experience remains significant. This study calls for prompt and effective strategies to rectify the nursing faculty shortage, ensuring optimal learning experiences for student nurses.